2020
DOI: 10.1101/2020.10.28.20221226
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The characteristics of HIV-positive patients with mild/asymptomatic and moderate/severe course of COVID-19 disease – a report from Central and Eastern Europe

Abstract: Background There is currently no evidence suggesting that COVID-19 takes a different course in HIV-positive patients on antiretroviral treatment compared to the general population. However, little is known about the relation between specific HIV-related factors and the severity of the COVID-19 disease. Methods We performed a retrospective analysis of cases collected through an on-line survey distributed by the Euroguidelines in Central and Eastern Europe Network Group. In statistical analyses characteristics o… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
1
7
0
1
Order By: Relevance
“…The patient living with HIV had great concerns about whether they are at high risk for the pandemic and the worse outcomes if they get infected with COVID-19. Research ndings on these concerns have been in agreement with previous studies conducted elsewhere [18,19,[33][34][35][36]. Studies indicated that though the pandemic affected the health care for all disease conditions, chronic patients such as people living with HIV are likely to be uniquely vulnerable [4,37,38].…”
Section: Discussionsupporting
confidence: 85%
“…The patient living with HIV had great concerns about whether they are at high risk for the pandemic and the worse outcomes if they get infected with COVID-19. Research ndings on these concerns have been in agreement with previous studies conducted elsewhere [18,19,[33][34][35][36]. Studies indicated that though the pandemic affected the health care for all disease conditions, chronic patients such as people living with HIV are likely to be uniquely vulnerable [4,37,38].…”
Section: Discussionsupporting
confidence: 85%
“…Although antiretroviral drug-induced pancreatitis can be observed in HIV-positive patients, it is highly unlikely in presented case as the patient was on well tolerated cART since 2016 (10). Whether and to what extent HIV remains a factor in the course and clinical presentation of SARS-CoV-2 infection remains unknown (11).…”
Section: Discussionmentioning
confidence: 85%
“…Ograniczenia w dostępie do opieki medycznej w czasie pandemii SARS-CoV-2 przełożyły się także na dostęp do diagnostyki w kierunku HIV (1,2). Od marca do czerwca 2020 wszystkie Punkty Konsultacyjno-Diagnostyczne, gdzie wykonywane są bezpłatne i anonimowe testy w kierunku HIV, były zamknięte.…”
Section: Wstępunclassified
“…Restricted access to healthcare during the SARS-CoV-2 pandemic also translated to limited access to HIV testing (1,2). From March to June 2020, all Counselling and Testing Centres that offer free and anonymous HIV tests were closed.…”
Section: Introductionmentioning
confidence: 99%